2019
DOI: 10.1097/cm9.0000000000000056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nighttime and daytime operation on outcomes of kidney transplant with deceased donors

Abstract: Background: Kidney transplant is always emergent operations and frequently need to be performed at nighttime to reduce cold ischemia time (CIT). Previous studies have revealed that fatigue and sleep deprivation can result in adverse consequences of medical procedures. This study aimed to evaluate whether nighttime operation has adverse impact on kidney transplant. Methods: A retrospective analysis of recipients accepted kidney transplant from deceased donors in one cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…That time is crucial, with a transfer of all the perioperative informations between teams, and can lead to transmission error. Giugale et al 18 showed an increase surgery time in the nurse handoff period, but no major CD complications associated during that time. Other studies reported higher risk of postoperative complications or even mortality when anaesthetic handover was done during cardiac surgery.…”
Section: Discussionmentioning
confidence: 95%
“…That time is crucial, with a transfer of all the perioperative informations between teams, and can lead to transmission error. Giugale et al 18 showed an increase surgery time in the nurse handoff period, but no major CD complications associated during that time. Other studies reported higher risk of postoperative complications or even mortality when anaesthetic handover was done during cardiac surgery.…”
Section: Discussionmentioning
confidence: 95%
“…First, a human factor can be at play: Less efficiency of the surgeon and/or medical care in the night period might induce prolonged ischemia duration and higher rates of technical failure. The few studies that previously investigated the impact of off-duty kidney transplantation did not show consistent data supporting such a fatigue effect [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Although Flechner et al showed that transplantations performed between 8 pm and 8 am result in a higher risk for 5-year graft failure [ 2 ], Özdemir-van Brunschot et al did not report such an off-hour impact in a larger population with an unexpected lower incidence of pure technical graft failure at night [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, off-hour surgery may result in lower performance of medical care due to staff fatigue. The net result of these two opposing factors on outcomes has only been explored in a few small studies focusing on graft declamping time-of-the-day, which reported inconsistent, and sometimes counter-intuitive results (e.g., less technical failure at night) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Importantly, time-of-the-day has been demonstrated to impact organ tolerance to IR injury [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] In addition, in a paper [ 34 ] that surveyed 27,305 cardiac surgery patients between 2010 and 2017 to compare morning and afternoon cardiac surgeries (procedures that included coronary artery bypass graft with internal mammary, or thoracic artery and vein or radial artery bypass) in regard to surgical site infections and mortality, the conclusion was that current evidence is not enough to favor afternoon cardiac surgeries, and that increased rates of morning myocardial infarction were not associated with an impact on the 1-year deep surgical site infections or mortality rate. Furthermore, there are a number of studies [ 35 37 ] of different transplant surgical procedures that have concluded that there is no higher risk, no poorer outcomes, and no adverse complications during nighttime surgeries compared to daytime.…”
Section: Discussionmentioning
confidence: 99%